Neisseria gonorrhoeae isolated at St. Mary's Hospital London, 1980-91. Issue 4 (August 1993) - Renton, A M; Ison, C A; Whitaker, L; Kirtland, K; Kupek, E; Harris, J R
Abstract : OBJECTIVE--To describe and discuss the trends in the isolation of Neisseria gonorrhoeae from patients attending the Genitourinary Medicine Clinic at St. Mary's Hospital, Paddington, London between 1980 and 1991. DESIGN--A retrospective study of the total number of gonococci isolated over an eleven year period was performed. In addition, for the years 1988-1991 the number of isolates from homosexual men was analysed by age of the patient, site of infection and HIV antibody status of the patient. RESULTS--The total number of N. gonorrhoeae isolates identified declined markedly between 1980 and 1989 from 3670 to 750 isolates. Over the same time period the number of specimens screened for N. gonorrhoeae fell by 50%. In 1990 there was an increase in N. gonorrhoeae isolates but this was not maintained, and in 1991 the number of N. gonorrhoeae fell to its lowest level of 638 isolates. The decrease since 1980 occurred in both men and women although the number of rectal isolates from men showed a steeper decline reaching its lowest level of 24 isolates in 1988. The number of rectal isolates from homosexual men has since increased with a peak in 1990. Many of the infections among homosexual men occurred in older men and included insignificant number of patients who were HIV positive. CONCLUSION--Gonorrhoea among attenders at St. Mary's Hospital has declined dramatically since 1980 following trends reported from much of Europe. The increase in gonococcal isolates since 1989 and the peak in 1990 are unexplained but are coincident with a higher number of isolates from homosexual men.